2006
DOI: 10.1097/01.hjh.0000239286.02389.0f
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of prehypertension and hypertension in a Korean population: Korean National Health and Nutrition Survey 2001

Abstract: Hypertension and prehypertension are common in Korea, and more than one-half of the hypertensive patients have not been diagnosed. These results place great emphasis on the urgent need for a public health program to improve the detection, prevention and treatment of hypertension and prehypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
83
8
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(117 citation statements)
references
References 36 publications
24
83
8
2
Order By: Relevance
“…The combined prevalence of preHT and HT (76.2%) was greater than that found in other studies 6,8 and lower than that found in a survey in China. 27 The analysis of the prevalence of HT alone in Florianópolis (41%) was higher than that of Italy, 25 Switzerland, 25 USA, 25 Canada, 25 Mexico, 20 Venezuela, 20 Chile, 20 Ecuador 20 and South Korea, 6 but was lower than that of Germany, 25 Finland, 25 Turkey, 8 Spain 25 and Cuba 20 and similar to that of England.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…The combined prevalence of preHT and HT (76.2%) was greater than that found in other studies 6,8 and lower than that found in a survey in China. 27 The analysis of the prevalence of HT alone in Florianópolis (41%) was higher than that of Italy, 25 Switzerland, 25 USA, 25 Canada, 25 Mexico, 20 Venezuela, 20 Chile, 20 Ecuador 20 and South Korea, 6 but was lower than that of Germany, 25 Finland, 25 Turkey, 8 Spain 25 and Cuba 20 and similar to that of England.…”
Section: Discussioncontrasting
confidence: 52%
“…27 The analysis of the prevalence of HT alone in Florianópolis (41%) was higher than that of Italy, 25 Switzerland, 25 USA, 25 Canada, 25 Mexico, 20 Venezuela, 20 Chile, 20 Ecuador 20 and South Korea, 6 but was lower than that of Germany, 25 Finland, 25 Turkey, 8 Spain 25 and Cuba 20 and similar to that of England. 25 PreHT and HT were strongly associated with being male, confi rming previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiovascular and cerebrovascular diseases are important causes of death in the Republic of Korea, as well as in many other countries. The most recent Korean National Health and Nutrition Examination Survey (KNHNES) showed that 22.9% of known hypertensive patients are now using antihypertensive medication, but hypertension is being adequately controlled in only 10.7% of those individuals (24). The control rate in the elderly population seems to be better than that in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Overweight and obesity are related to a number of health consequences, including type two diabetes, coronary heart disease, stroke, hypertension, gallbladder disease, and certain types of cancer, sleep apnea, psychosocial disturbances and osteoarthritis (8). Some recent studies also revealed that overweight and obesity are the main risk factors for prehypertension (9)(10)(11)(12). There are few data on the epidemiology of overweight and obesity in the county of China.…”
Section: Introductionmentioning
confidence: 99%